Analisis Dampak Program Makan Bergizi Gratis Terhadap Peningkatan IQ Siswa (Studi pada SDN 3 Mataram) - Wawan Saputra (STAI AL-AMIN, 2026)
The Free Nutritious Meal Program is a nutritional intervention aimed at supporting the cognitive development of elementary school-aged children. This study aims to analyze the implementation of the Free Nutritious Meal Program and examine its impact on improving student IQ at SDN 3 Mataram. This study used a quantitative descriptive approach with an ex post facto design. The study population was all 215 students at SDN 3 Mataram, with a sample size of 93 students from grades IV, V, and VI, determined using a purposive sampling technique. Data collection was conducted through questionnaires to measure the implementation of the Free Nutritious Meal Program and a basic IQ test to assess students' cognitive abilities. Data analysis was performed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) 4.1.1.6 method to simultaneously examine the relationships and influences between variables. The results indicate that the implementation of the Free Nutritious Meal Program at SDN 3 Mataram is categorized as good based on student perceptions, with an average score of 4.16. Meanwhile, students' perceptions of IQ improvement were in the good category, with an average score of 4.09. The results of the inferential analysis using SEM-PLS showed that the Free Nutritional Meal Program had a positive and significant effect on student IQ improvement, with a total effect value of 0.800 and a p-value of 0.000 (<0.05). Based on these findings, it can be concluded that the Free Nutritional Meal Program not only plays a role in meeting students' nutritional needs but also makes a significant contribution to improving their cognitive abilities and intellectual intelligence. Therefore, this program is worthy of being maintained and developed as part of a strategy to improve the quality of human resources starting from elementary school age. Keywords: Free Nutritional Meal Program, Student IQ, Child Nutrition, SEM-PLS, Elementary School